PENGGUNAAN MEDIA GAMBAR TERHADAP PENINGKATAN KETERAMPILAN MEMBACA SISWA KELAS IV MADRASAH IBTIDAIYAH MA’HAD AL-ZAYTUN - Amrina Rosyada Melenia; Iis Humaeroh; Dede Indra Setiabudi (STKIP Subang, 2025)
This study aims to analyze the effect of using picture media on improving the reading skills of fourth-grade students at Madrasah Ibtidaiyah Ma’had Al-Zaytun, Indramayu. The main problem addressed is the low reading ability of students, as reflected in their learning outcomes before the treatment. This research employed a quantitative approach with a pre-experimental design of the One Group Pretest-Posttest type. The research sample consisted of 36 students selected from two classes, IV-B05 and IV-B08. The research instrument was an objective multiple-choice test consisting of 15 items, administered as pretest and posttest. Data were analyzed using descriptive and inferential statistics, including normality tests, t-tests, and Wilcoxon tests. The results showed a significant improvement in students’ reading skills after the implementation of picture media. The average posttest scores were higher than the pretest, the number of students achieving good and excellent categories increased, while the number of students in the low category decreased considerably. Hypothesis testing also confirmed a significant difference between the results before and after the treatment. In addition to quantitative improvement, it was also found that students became more active, motivated, and confident in reading. Therefore, it can be concluded that picture media is effective as a learning strategy to enhance the reading skills of elementary school students. Keywords: picture media, reading skills, elementary school students, Indonesian language learning;